Peran Interaksi Guru dalam Meningkatkan Motivasi Belajar Siswa - Megawati Gulo; Indah Karyani Zega; Nika Tri Warna Lase; Lestari Waruwu (Journal on Education, 2023)
This study aims to: (1) describe the role of teacher interaction in increasing student motivation; (2) identify the teacher's challenges in increasing student motivation; and (3) providing new knowledge and perspectives to educators about the teacher's role in increasing student learning motivation. Descriptive qualitative research methodology was used in this study to collect data through observation, interviews, and record keeping. The theoretical basis that is used as a research guide is in accordance with the reality in the regions included in the results and discussion. Grade VIII students and one of the teacher were used as research participants for learning at SMP Negeri 1 Moro'o. The problem of this research is motivation increases student learning through the role of the teacher. The research findings show that teachers have succeeded in improving their roles as mentors, instructors, and class leaders as well as motivating students to learn.